SOA Services Identification and Design Methods From Business Models: A Systematic Literature Review - Redouane Blal; Abderrahmane Leshob; Hafedh Mili; Imen Benzarti; Pierre Hadaya; Raqeebir Rab (IEEE Access)
Modern organizations are process-oriented. To remain competitive in the digital transformation era, these organizations design and implement Information Systems (IS) to support their business processes. The emergence of the Service-Oriented Architecture (SOA) style made it possible to design IS architectural models that meet software quality criteria and are aligned with the organizations’ business models. However, designing such SOA services is a complex task that requires extensive knowledge and skills in software architecture and the business domain. Researchers and practitioners have proposed several methods to derive SOA services from business models during the last two decades. However, SOA design initiatives from business models still fail. Existing methods and processes to design process-aware IS have limitations related to their usability and implementation complexity. These limitations triggered the necessity for a survey that extracts more information about how to design SOA architectural models from business models. This work proposes a systematic literature review (SLR) to establish the state of the knowledge about the existing methods that derive service models from business models. This SLR provides practitioners, such as solutions architects, business architects, and application architects, a comprehensive overview of available methods to derive SOA architectural models from business models, helping them design SOA services and build effective software solutions. We selected forty-one primary studies published between 2006 and 2023. We compared selected methods according to seven specific criteria, namely: design life cycle coverage, detailed specification support, SoaML support, service granularity, the use of patterns, automation, and tool support. The results confirm that SOA is an established architectural style for building effective ISs that support organizations’ business processes. As far as we observed from comparing selected methods according to the selected criteria, our findings explain the need for a new method that provides organizations with an easy-to-use and comprehensive process to derive quality SOA models from business models.